Cryptocurrency exchange landscape in the EU How regulation impacts success of cryptocurrency exchanges - Szepesi, Laura (2020)
Ever since the emergence of digital assets, bitcoin (BTC) and other crype to currencies created huge debates and discussions globally. Demand has transformed trading opportunitis in the digital era, and anew ecosystem has been created around cryptocurrencies. Not only the coins, but the underlying technology has found many applications worldwide as well, especially in the financial markets.However, since the market infrastructure is growing expeditiously,regulations have a hard time keeping up with the speed of innovation. Merging this complex and fast evolving area into the established traditional legal framework has already proved to be a difficult and lengthy process. Due to the absence of a global harmony in the regulatory frameworks, digital service providers can take advantage of the regulatory arbitrage. In order to maximize profitability, the decision on how to cope with the regulatory framework can be crucial for any service provider.The attitude towards regulation in this environment is just as fragmented as the legislations itself. Founder and CEO of bit Flyer, Yuzo Kano made an announcement at the opening of the European office of bitFlyer:”When I set up bit Flyer in 2014, I did so with global ambitions and the belief that approved regulatory status is fundamental to the long-term future of Bitcoin and the virtual currency industry. I am proud that we are now the most compliant virtual currency exchange in the world; this coveted regulatory status gives our customers, our company and the virtual currency industry as a whole a verypositive future outlook[1].”A completely different approach was expressed by the CEO of Binance,Chang peng Zhao:“If you do fiat to crypto [. . . ] you have to have a bank account that can accept money,” he says. “That has its own advantages and problems. You have to deal with regulatory issues and usually you’retied to one country.”The more you deal with fiat, the more[authorities] can control you,” says Zhao. “The bank will freeze your bank account. They can make the wire transfer slow”[44].The strategical decisions of digital currency exchanges can be de-rived from their view on regulation. This paper will examine some of the top exchanges with a regional footprint in the European Union(EU). Furthermore, the impact of regulation on crypto exchanges will be analysed, based on the exchanges’ strategy and different success factors. The diversity of jurisdictions covered by this paper provides also an overview how various governments have approached regulat-ing digital exchanges. Even though the cryptocurrency market out-side of Europe should not be underestimated, this paper focuses on the comparative analysis on digital exchanges operating within the EU. Including other exchanges would alter the conclusion since the quoted crypto-fiat pairs, users, and many other factors diverge from the European landscape.The expectation is to conclude that regulatory compliant digital exchanges are more successful on a long-term perspective.